The relationship between tourism development and sustainable development goals in Vietnam - Liu, Lishan; Abdullah, Nawal Hanim; Ramachandran, Sridar; Raja Yusof, Raja Nerina (Universidad Autonoma de Madrid, 2021)
This study explores the relationship between tourism development and sustainable development goals in Vietnam. This study takes tourism receipt and tourism expenditures as indicators to measure the level of tourism development, while government environmental expenditures have been used to measure sustainable development. This study also uses population growth and economic growth as control variables in the study. This study has extracted the data from World Bank Indicators (WDI) from 1971 to 2019. The study employs the unit root test to examine the stationarity of the variables and also uses the autoregressive distributed lag (ARDL) model to investigate the relationships among the variables. This study finds a positive association between tourism development and sustainable development goals in Vietnam. In doing so, it is able to provide insightful guidance for policymakers seeking to formulate and implement policies related to tourism development and sustainable development.